Lexico-Semantic Analysis of News Reports in Okexone.com and Tribunnews.com about World War III Issues - Melati Nuraini Putri; Fitrawati Fitrawati (Universitas Negeri Padang, 2020)
Although there have been various semantics studies of news reports, so far the use of lexico-semantics approach in analysing news reports has not been common. The aim of this research is analyze the lexical relations and meaning properties in news reports. It was carried out descriptive-qualitatively. Eight news reports in Okezone.com and eight news reports in Tribunnews.com were studied by using Saeed’s (2009) theory of lexical relations and Siregar (1992) and Leech’s (19981) theory of meaning properties. After completing the analysis, it was found that news news reports in Tribunnews.com are slightly different with the news reports in Okezone.com. There are six types of lexical relations in Tribunnews.com: hyponymy, polysemy, homonymy, synonymy, antonymy, and metonymy, while there are only five types of lexical relations in Okezone.com: hyponymy, polysemy, synonymy, antonymy, and metonymy. In addition, there are five types of meaning properties in Tribunnews.com: meaningfulness, ambiguity, redundancy, anomaly, and contradictory, while there are only four types of meanin properties in Okezone.com: meaningfulness, ambihuity, redundancy, and anomaly.